Internalization of the Values of Religious Moderation in Islamic Religious Education at State Senior High School 2 Pinrang - Muhammad Mukhtar S (International Journal on Advanced Science, Education, and Religion, 2024)
This research aims to analyze the internalization of religious moderation values in Islamic religious education at State Senior High School 2 Pinrang. The study uses a qualitative approach with a focus on in-depth exploration of social phenomena through phenomenological methods. Data sources include the principal, teachers, and students selected using purposive sampling techniques. Data were collected through participant observation, in-depth interviews, and document studies, and analyzed using data reduction, data presentation, and conclusion drawing techniques. The results of the study indicate that the values ​​of religious moderation applied at State Senior High School 2 Pinrang include tolerance, humanity and equality, national commitment, and accommodation of local culture. The process of internalizing these values ​​is carried out through learning integration (hidden curriculum), by linking diversity issues to teaching materials. Through interactive learning through group discussions and case studies. Teacher role models who demonstrate moderate attitudes and share experiences related to moderation practices. Extracurricular activities through diversity-themed competitions. Comprehensive evaluation, covering cognitive, affective, and psychomotor aspects. The development of Islamic religious education based on moderation in State Senior High School 2 Pinrang is carried out through the integration of moderation values ​​in the curriculum, training and improving teacher competencies, implementing active learning methods, strengthening extracurricular activities that support moderation, and ongoing evaluation and monitoring